Urban environment friendliness in the perspective of a structural functionalism - Lebedeva, Еlena V.; Filipova, Aleksandra G. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is devoted to the sociological analysis of the urban environment in the perspective of the structural functionalism theory. A review of modern theoretical approaches exploring the post-soviet cities environment friendliness is given with evaluating their advantages and disadvantages. The expediency of the use of structural-functional analysis as a methodological principle of empirical study of the city is substantiated. The post-Soviet city is considered as a sociocultural system, the causes and consequences of the appearance of dysfunctions in it are analyzed. An original author’s functional model of a friendly urban environment is constructed, which allows to overcome the existing limitations of an empirical measurement of the quality of the urban environment, and can also form the basis for building a universal system of principles for designing a city.
Keywords: city; urban environment; structural and functional analysis; post-soviet cities; functions of the urban environment; friendly urban environment